Photoacoustic imaging at 1064 nm wavelength with exogenous contrast agents - Upputuri, Paul Kumar (2018)
Photoacoustic (PA) imaging is a promising imaging modality for both preclinical research and clinical practices. Laser wavelengths in the first near infrared window (NIR-I, 650-950 nm) have been widely used for photoacoustic imaging. As compared with NIR-I window, scattering of photons by biological tissues is largely reduced in the second NIR (NIR-II) window, leading to enhanced imaging fidelity. However, the lack of biocompatible NIR-II absorbing exogenous agents prevented the use of this window for in vivo imaging. In recent years, few studies have been reported on photoacoustic imaging in NIR-II window using exogenous contrast agents. In this work, we discuss the recent work on PA imaging using 1064 nm wavelength, the fundamental of Nd:YAG laser, as an excitation wavelength. The PA imaging at 1064 nm is advantageous because of the low and homogeneous signal from tissue background, enabling high contrast in PA imaging when NIR-II absorbing contrast agents are employed.